Mass Diffusion Metamaterials with "Plug and Switch" Modules for Ion Cloaking, Concentrating, and Selection: Design and Experiments. Issue 30 (17th August 2022) - Li, Yang; Yu, Chengye; Liu, Chuanbao; Xu, Zhengjiao; Su, Yanjing; Qiao, Lijie; Zhou, Ji; Bai, Yang
Abstract: The outstanding abilities of metamaterials to manipulate physical fields are extensively studied in both wave‐based and diffusion‐based fields. However, mass diffusion metamaterials, with the ability to manipulate diffusion with practical applications associated with chemical and biochemical engineering, have not yet been experimentally demonstrated. In this work, ion cloaking, concentrating, and selection in liquid solvents are verified by both simulations and experiments, and the concept of a "plug and switch" metamaterial is proposed based on scattering cancellation (SC) to achieve switchable functions by plugging modularized functional units into a functional motherboard. Plugging in any module barely affects the environmental diffusion field, but the module choice impacts different diffusion behaviors in the central region. Cloaking strictly hinds ion diffusion, and concentrating increase diffusion flux, while cytomembrane‐like ion selection permits the entrance of some ions but blocks others. In addition, these functions are demonstrated in special applications like the catalytic enhancement by the concentrator and the protein protection by the ion selector. This work not only experimentally demonstrates the effective manipulation of mass diffusion by metamaterials, but also shows that the "plug and switch" design is extensible and reconfigurable. It facilitates novel applications including sustained drug release, catalytic enhancement, bioinspired cytomembranes, etc. Abstract : Modular mass diffusion metamaterials with reconfigurable functions are designed. The ability to manipulate mass diffusion behavior in a liquid solvent to realize cloaking, concentrating, and selection are experimentally verified. The effective manipulation of mass diffusion behavior by mass diffusion metamaterials can further spawn applications in chemical and biological engineering, such as catalytic enhancement and protein protection.